PENINGKATAN HASIL BELAJAR SISWA DALAM MENGUNKAPKAN EXPRESSION OF SYMPATHY MELALUI MODEL PMPDR DAN APLIKASI TEACHMINT - MUHAMMAD DANIAL (Pusat Pengembangan Pendidikan dan Penelitian indonesia (P4I), 2022)
The 2013 curriculum has been applied in learning in every educational unit, including at SMP Negeri 2 Bontomarannu, but some problems still continue to arise in the process of learning English at SMP Negeri 2 Bontomarannu. One of the crucial problems is that students do not understand and are less able to practice English learning theory, especially the subject matter of expressing expressions of sympathy. Finally, the researchers tried to improve student learning outcomes on the subject matter of expressing expressions of sympathy through the application of the PMPDR learning model and the Teachmint application. This type of research is classroom action research which aims to improve the learning outcomes of class IX.B students of SMP Negeri 2 Bontomarannu in learning English through the application of Preactivity, Main activity, Post Activity, Demonstration and Reinforcement (PMPDR) learning models and Teachmint application. The subjects of this study were students of class IX.B SMP Negeri 2 Bontomarannu with 26 students consisting of 12 female students and 14 male students. This research was conducted in two cycles, namely the first cycle was conducted 2 times and the second cycle was also 2 meetings, which was conducted for 2 months. The result is an increase in student learning outcomes through the Preactivity, Main activity, Post Activity, Demonstration and Reinforcement (PMPDR) learning models and the Teachmint Application. The details of the research results are the learning outcomes of class IX.B students of SMP Negeri 2 Bontomarannu in the first cycle in the high category with an average score of 75 while in the second cycle there is a significant increase in the very high category with an average value of 83. ABSTRAKKurikulum 2013 telah diterapkan dalam pembelajaran di setiap satuan pendidikan termasuk di SMP Negeri 2 Bontomarannu, namun beberapa permasalahan masih terus muncul dalam proses pembelajaran Bahasa Inggris di SMP Negeri 2 Bontomarannu. Salah satu permasalahan yang krusial adalah siswa tidak memahami dan kurang mampu mempraktekkan teori belajar Bahasa Inggris khususnya materi pokok ungkapkan expression of sympathy. Akhirnya peneliti berusaha mencoba meningkatkan hasil belajar siswa pada materi pokok ungkapkan expression of sympathy melalui penerapan model pembelajaran PMPDR dan Aplikasi Teachmint. Jenis penelitian ini adalah penelitian tindakan kelas (Classroom Action Research) yang bertujuan untuk meningkatkan hasil belajar Siswa kelas IX.B SMP Negeri 2 Bontomarannu dalam pembelajaran Bahasa Inggris melalui penerapan model pembelajaran Preactivity, Main activity, Post Activity, Demonstration and Reinforcement (PMPDR) dan Aplikasi Teachmint. Subyek penelitian ini adalah siswa kelas IX.B SMP Negeri 2 Bontomarannu dengan jumlah siswa 26 orang terdiri dari 12 orang siswa perempuan dan 14 orang siswa laki laki. Penelitian ini dilakukan dalam dua siklus yaitu siklus I dilakukan 2 kali pertemuan dan siklus II juga 2 kali pertemuan, yang dilakukan selama 2 Bulan. Hasilnya adalah terjadi peningkatan hasil belajar siswa melalui model pembelajaran Preactivity, Main activity, Post Activity, Demonstration and Reinforcement (PMPDR) dan Aplikasi Teachmint. Adapun rincian hasil penelitian adalah hasil belajar siswa kelas IX.B SMP Negeri 2 Bontomarannu pada siklus I masuk kategori tinggi dengan jumlah nilai rata rata 75 sedangkan pada siklus II mengalami peningkatan signifikan dengan kategori sangat tinggi dengan nilai rata-rata 83.